PENGETAHUAN PEKERJA SEKS KOMERSIAL (PSK) DALAM MENCEGAH PENYAKIT KELAMIN DI KOTA MANADO - Josef Kurniawan Kairupan, Philep Morse Regar (Universitas Sam Ratulangi, 2016)
Patients sexually transmitted diseases such as syphilis, hiv-aids and living in Kota Manado increasingly increase in line with the development of Kota Manado be metropolitan city, the transmission of disease is nowhere to be avoided, because the monetary crisis and an economy that have impacted systemic for social life, especially in the economic aspect. This would result in the increase the number of unemployment and finally into factors driving for labor to do anything to get the money although contrary to law, moral, and ethics for example steal, and work as prostitutes. Expected outcomes research is answering problems in accordance with a hoped, namely: changes in thinking about basic needs of the target groups (PSK, HIV AIDS patients / ODHA) include: needs to be protected of the security, comfort and health by making localization, in the implementation of the to formulate steps further policy. Intervene a way of thinking the public about existence of HIV AIDS and ODHA and the way to interact efficient. The involvement of religious figures considered a counterpart proper to help socialize the matter to the community remember the average person Manado submit to religious figures. Educational institutions to agent main to build human that characterless and pleaseth. Keywords: PSK, the spread of sex